Copper(I)‐Catalyzed Dehydrogenative Amidation of Arenes Using Air as the Oxidant. Issue 6 (16th March 2015) - Li, Gang; Jia, Chunqi; Chen, Qingliang; Sun, Kai; Zhao, Feng; Wu, Hankui; Wang, Zhiyong; Lv, Yunhe; Chen, Xiaolan
Abstract The copper(I) bromide‐catalyzed intermolecular dehydrogenative amidation of arenes via CH bond activation assisted by a 2‐pyridyl or 1‐pyrazolyl chelating group using air as the terminal oxidant has been achieved at 140 °C. N‐Aryl amides, N‐alkyl amides, benzamide derivatives, imides, and lactams all are good coupling partners to obtain moderate to excellent yields. The amount of solvent is critical for the transformation: both increasing and decreasing the amount of solvent decreased the yield. Notably, the amidation of bimolecular 2‐phenylpyridine with the dual NH bonds of a primary amide proceeded smoothly in one‐pot to afford a good yield under the same conditions. The amidation can be performed with a good yield at the gram scale. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>